Domesticity and dissent in the seventeenth century : English women's writing and the public sphere / Katharine Gillespie. - Gillespie, Katharine (Cambridge University Press, 2003)
In this work, Katharine Gillespie examines writings by 17th century English Puritan women who fought for religious freedom.